Associated minerals in chrysotile deposits and their potential health risks - Chatfield, Eric J. (Frontiers in Public Health, 2025)
Chrysotile samples from different deposits and the UICC-A and UICC-B standards have been analyzed by a procedure in which the chrysotile is removed by successive treatments in hydrochloric acid and sodium hydroxide, followed by transmission electron microscopy (TEM) examination of the residues. Two separate TEM fiber counts of a minimum of 100 fibers each were made for each sample: fibers longer than 5 μm and fibers with lengths between 0.5 μm and 5 μm. The tremolite/actinolite in each sample was quantified in terms of fibers/gram of chrysotile and as mass fraction in parts per million (ppm). Chrysotile from almost all of the commercial deposits examined was found to contain tremolite/actinolite. In particular, UICC-B Canadian chrysotile was found to contain an average of approximately 180 ppm tremolite/actinolite, equivalent to 1.25 × 107 fibers per gram (longer than 5 μm) of tremolite/actinolite, a proportion of which is asbestiform. The results also showed that both the UICC-B and UICC-A chrysotile standards are contaminated by Amosite. The primary grades of chrysotile from Coalinga, United States, and Minaçu, Brazil, were found to contain substantially less than 1 ppm of tremolite/actinolite. An asbestiform variety of the pyroxene diopside was detected in chrysotile from the Balangero mine in Italy. The asbestiform diopside has a fiber concentration and mass fraction comparable to those of tremolite/actinolite in chrysotile from other sources. Some of the diopside fibers are considerably longer than the tremolite/actinolite fibers found in other sources of chrysotile. Low levels (<4 ppm) of tremolite/actinolite were detected in Balangero chrysotile. No fibers with compositions consistent with Balangeroite were detected. It was found that Balangeroite does not survive the acid-alkali dissolution procedure, and it probably has durability comparable to that of chrysotile. Publications that claim the absence of tremolite/actinolite in UICC-B chrysotile were based on analytical methods that had insufficient sensitivity. Use of these analytical methods permitted only a 1 in 5 chance that a single tremolite/actinolite fiber would be detected. The concentrations of tremolite/actinolite and Amosite found in the reference UICC chrysotile standards raise questions as to the validity of historical biological experiments carried out using these materials.